Delay Discounting in Established and Proposed Behavioral Addictions: A Systematic Review and Meta-Analysis - Weinsztok, Sarah; Brassard, Sarah; Balodis, Iris; Martin, Laura E.; Amlung, Michael (Frontiers in Behavioral Neuroscience, 2021)
Steep delay discounting, or a greater preference for smaller-immediate rewards over larger-delayed rewards, is a common phenomenon across a range of substance use and psychiatric disorders. Non-substance behavioral addictions (e.g., gambling disorder, internet gaming disorder, food addiction) are of increasing interest in delay discounting research. Individual studies have reported steeper discounting in people exhibiting various behavioral addictions compared to controls or significant correlations between discounting and behavioral addiction scales; however, not all studies have found significant effects. To synthesize the published research in this area and identify priorities for future research, we conducted a pre-registered systematic review and meta-analysis (following PRISMA guidelines) of delay discounting studies across a range of behavioral addiction categories. The final sample included 78 studies, yielding 87 effect sizes for the meta-analysis. For studies with categorical designs, we found statistically significant, medium-to-large effect sizes for gambling disorder (Cohen’s d = .82) and IGD (d = .89), although the IGD effect size was disproportionately influenced by a single study (adjusted d = .53 after removal). Categorical internet/smartphone studies were non-significant (d = .16, p = .06). Aggregate correlations in dimensional studies were statistically significant, but generally small magnitude for gambling (r = .22), internet/smartphone (r = .13) and food addiction (r = .12). Heterogeneity statistics suggested substantial variability across studies, and publication bias indices indicated moderate impact of unpublished or small sample studies. These findings generally suggest that some behavioral addictions are associated with steeper discounting, with the most robust evidence for gambling disorder. Importantly, this review also highlighted several categories with notably smaller effect sizes or categories with too few studies to be included (e.g., compulsive buying, exercise addiction). Further research on delay discounting in behavioral addictions is warranted, particularly for categories with relatively few studies.